Enhancing Temperature Sensitivity Using Cyclic Polybutylene Terephthalate- (c-pbt-) Coated Fiber Bragg Grating - H. Ahmad; S. F. S. M. Noor; A. F. Arusin; S. A. Samsudin; K. Thambiratnam; W. Y. Chong; K. S. Lim; M. Z. Zulkifli (Hindawi Publishing Corporation, 2024)
Volume : 2018